Re-Design UI/UX IBS Core dengan Metode Design Thinking Untuk Meningkatkan Pengalaman Pengguna - Nanik Sugiyarti; Rofi Abul Hasani; Nuryanto (STMIK Budi Darma, 2023)
With advances in information technology, the banking industry has experienced major changes in providing banking services. The Core banking system is the basis for modern banking operations, enabling banks to integrate important functions such as account management, transaction processing, risk management and financial reporting. However, based on the results of observations and interviews, application users still feel uncomfortable when using it. Therefore, researchers have developed several ideas and solutions as a guide in designing the Core banking system application user interface. One of the ideas and solutions generated is to focus on improving the user experience by updating the appearance of the application to make it more attractive and responsive, as well as arranging a more efficient navigation menu layout. This research focuses on the application of Design Thinking as a comprehensive thinking approach to achieve the desired solution. This research was conducted through several stages of Design Thinking, namely empathize, define, ideate, prototype, and testing. The results of the User Experience Questionnaire (UEQ) show an average value of 2.23. Four parameters in the